Crystal structure of bis(ethanaminium) poly[bis(hexaselenido-κ2Se1,Se6)palladate(II)], C4H16N2PdSe12 - Kim Kang-Woo; Wang Di (Zeitschrift für Kristallographie - New Crystal Structures, 2016)
C4H16N2PdSe12, monoclinic, C2/c (No. 15), a = 16.8578(5) Å, b = 7.6646(2) Å, c = 16.7440(5) Å, β = 94.7894(15)°, V = 2155.91(11) Å3, Z = 4, Rgt(F) = 0.0351, wRref(F2) = 0.0722, T = 173 K.